Antecedent Analysis of Household Consumption of Family Hope Program (FHP) Recipients in Lepadi Village, Pajo District, Dompu, West Nusa Tenggara, Indonesia - Siti Amalia; Agus Iwan Kesuma (Technium Social Sciences Journal, 2025)
This study aims to analyze antecedent factors that affect the consumption of households receiving the Family Hope Program (FHP) in Lepadi Village, Pajo District, Dompu, West Nusa Tenggara. The factors studied included smoking status, private vehicle ownership, productive asset ownership, and land and property ownership. The approach used in this study is quantitative with an explanatory design. The research sample consisted of 45 FHP recipient households who were selected purposively. Data was collected through a questionnaire that measured respondents’ perceptions of the variables studied using the Likert scale. The analysis method used is multiple linear regression to test the influence of independent variables on household consumption as a dependent variable. The results showed that smoking status factors significantly affected household consumption, while private vehicle ownership, productive assets, and land and property had no significant effect